An effective pedagogical practise for integrating HIV and AIDS into tertiary education: An Interior Design case study - Gill, A.; Di Monte-Milner, G. (South African Journal of Higher Education, 2017)
This article discusses a pedagogical practise used to introduce HIV and AIDS content into an existing Interior Design curriculum from a creative praxis perspective. Curriculum-integration is a key strategy of the Higher Education HIV/AIDS Programme (HEAIDS), which was established to develop and support HIV-mitigation programmes at South Africa’s public Higher Education Institutions. Students within the Faculty of Art, Design and Architecture at the University of Johannesburg engaged in a spatial intervention project that was structured around project-based learning strategies and constructivist teaching values. Students’ proposals were analysed against their ability to promote HIV and AIDS prevention and create appropriate meaning amongst the target group. The paper suggests that the methodology proved effective because it did not require radical curriculum transformation; aligned with existing programme outcomes; and demonstrated potential to contribute to the ‘new literacy of AIDS’ required to counter ‘AIDS fatigue’.